The Antecendents Of Innovative Work Behavior: Concepts And Dimensions - Iffah Rosyiana; Intan Fauzi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
The study aims of this article is to propose a definition, identify dimensions and concepts of innovative behavior in lecturers. Innovative work behavior means all lecturer behavior regarding ideas in general, promotion and implementation of new ideas, processes, products or procedures in the lecturer's work. The concept and definition of "Innovative Work Behavior" is more specifically carried out by teacher and lecturers in a specific and clear context. Discover several dimensions of the concept of innovative behavior from various views. Antecendents of innovative work behavior can be categorized, namely from individual, job characteristics, social characteristics and organizational factors. The method used is a systematic meta-analysis review of several articles from Researchgate, Ed.gov, Sinta, etc. There are several challenges in research to produce innovative work behavior towards lecturers, especially in providing definitions and dimensions.